Determinan Kemiskinan Provinsi Jambi - Irmanelly; Devita.Andri; Indria Mayesti; Nurdin (Fakultas Hukum dan Ekonomi Bisnis, 2021)
The research entitled Determination of Poverty in Jambi Province uses secondary data which is presented in the form of annual data / series from 2000-2019, which were obtained from BPS RI, BPS Jambi Province and Jambi Province Bappeda. The analysis tool uses the Multiple Regression Model Analysis model and Pearson Correlation using software views 8.0 and SPSS version 21.0. The results showed that 1). Economic growth (GE) and human development index (HDI) partially have a negative and significant effect in reducing poverty in Jambi Province, while the productive population (JP) has a positive and significant effect on increasing poverty in Jambi Province during the 2000-2019 period. Meanwhile, expenditure per capita and labor force did not significantly influence the increase or decrease in poverty in Jambi Province during the 2000-2019 period. However, simultaneously economic growth, per capita expenditure, population, human development index and labor force have a significant effect on the fluctuation of poverty in Jambi Province with a R-squared of 87.00 percent. 2). The relationship between economic growth, per capita expenditure, population, human development index and labor force with poverty in Jambi Province as a whole is very strong with a correlation coefficient of 92.3 percent. Individually, government spending (PP), the number of productive population (JP) and the working labor force (AK) with poverty in Jambi Province